2019
DOI: 10.1111/jonm.12822
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction and related factors of nurses in university hospitals: Focusing on collaborative competency factors

Abstract: Aim:This study aimed to clarify the association between nurses' job satisfaction, interprofessional collaborative competency and other related factors in university hospitals in Japan. Background:Enhancing a team's function in the university hospital setting requires strengthening each professional's competency: high-level professional competency leads to high job satisfaction. Methods:In 2014, self-administered questionnaires were sent to all nurses working at two university hospitals in Japan. A multivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 27 publications
0
15
0
5
Order By: Relevance
“…Meanwhile, the mean for professional autonomy among nurses acting as PAs was remarkably lower than staff nurses’ in similar cultural contexts (e.g., Japan [ 61 ] and China [ 62 ]) and also in Western contexts [ 63 , 64 ] when comparing the findings on the same instrument. This could be attributed to confusion about professional identity among Korean nurses acting as PAs [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 98%
“…Meanwhile, the mean for professional autonomy among nurses acting as PAs was remarkably lower than staff nurses’ in similar cultural contexts (e.g., Japan [ 61 ] and China [ 62 ]) and also in Western contexts [ 63 , 64 ] when comparing the findings on the same instrument. This could be attributed to confusion about professional identity among Korean nurses acting as PAs [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 98%
“…Contrary to this result, some studies reported that job satisfaction of nurses differed according to the unit. 1,15,35,36 Majima et al 37 found that job satisfaction of intensive care nurses was lower than that of nurses in other units. In our study, factors that could affect job satisfaction were not investigated and this may have affected this result.…”
Section: Effects Of Nurses' Characteristics On Their Perceived Support and Job Satisfaction Levelsmentioning
confidence: 99%
“…The ABP subscale indicates values and identity as a professional. Majima et al (26) found that nurses in their study valued their work highly and this has led to increase job satisfaction. The TMS, ATG, ABTC, and FRP subscales relate to teamwork.…”
Section: Discussionmentioning
confidence: 88%